Closer shipper-liner partnership : shipper's perspective - Sun, Qian. (2009)
Shipper-Liner Partnership can bring competitive advantages in the marketplace for both parities. Hence, it is moving towards the center stage in the analysis of closer shipper-liner partnership, especially in today’s continually changing and uncertain business environment. This paper presents a thorough study on closer shipper-liner partnership from shipper’s perspective. Through survey, shippers’ (from electronics, apparel, automotive, perishable foods and furniture industries) insights on current relationship with liners and critical success attributes for shipper-liner partnership are collected. The current partnership can be classified under Type II partnership, which has a relatively longer term in nature, some investment from either party as well as a larger scope of joint activities. However, most shippers are generally not satisfied with their current partnerships with liners. Surprisingly, shippers from all industry agree on what are the most important partnership success attributes, with commonly agreed top five attributes being cost focus, flexibility, trust, communication and effectiveness. Nonetheless, those attributes that root in the foundation of partnership, such as strategic fit, planning and investment have not been taken much care of by shippers. Hence, shippers are still towards result-oriented rather than emphasizing on building up foundation of relationship with long-term focus. On the other hand, the satisfaction rates on each attribute fluctuate a lot among different shippers, which also lag far behind from the importance rates. Analysis on successful partnership attributes is conducted individually, and recommendation on how to improve partnership from each attribute has been provided. At the conclusion part, the author joins recommendations on all attributes together and recommends the way to develop true partnership (Type III partnership) in the sequence of partnership development stages.